The Unrealized Power Of Mother - Roberts, Dorothy E. (Columbia Journal of Gender and Law, 1995)
In The Neutered Mother, The Sexual Family and Other Twentieth Century Tragedies, [Martha Albertson Fineman] dares to assert that motherhood has an unrealized power. 1 It is essential, she declares, for feminists to reclaim the term. 2 Her admonition could not be more timely. As Fineman powerfully demonstrates throughout the book, contemporary political discourses about single mothers, especially in the contexts of welfare and divorce, increasingly cast women’s independent mothering as pathological. 3 At the same time, policies that reinforce the norm of the private nuclear family leave women with the burdens of caretaking while denying them both needed public support and privacy from government intrusion. 4 Fineman’s analysis helps to explain the key elements of current welfare reform proposals–the vilification of single mothers as the cause of poverty and social degeneracy; stepped-up government regulation of their intimate lives; and imposition of private measures such as paternal child support and marriage as the solution to children’s poverty. The Neutered Mother shifts attention from the marital couple to mothers and their children as the family unit that merits social assistance and legal protection, and as the center of feminist inquiry and activism. It is a long-overdue demand for society to value concretely the roles that women undertake and to compensate them for the hard work that they perform. Fineman very successfully refutes both the stigma attached by policymakers to single mothers, as well as the criticism by some feminists of the focus on motherhood. By calling motherhood an unrealized power, however, Fineman seems to imply more than a defensive move. Throughout the book there is the suggestion that motherhood is a positive force, perhaps even a liberating occupation, for women. Although Fineman astutely observes that physical dependency is inevitable, in that it flows from the status and situation of being a child and often accompanies aging, illness, or disability, 15 she barely questions whether or not it is inevitable that women be caretakers. Fineman does not critique women’s role as mother as she does women’s role as wife. In her chapter on the sexual family, for example, Fineman notes that most of the girls interviewed for a survey were far less committed than boys to the idea of getting married. More than half of the girls stated that they would consider becoming a single parent. Fineman quotes one sixteen-year old’s response: If I weren’t married, I could imagine being a single mother. I know it’s hard, but it’s worth it. I just know I want children. 16 Fineman emphasizes the gender differences in the teenagers’ expectations for marriage, but does not question the girls’ assumption that they will become mothers. Moreover, Fineman is firm in her selection of the Mother/Child dyad as the central intimate connection, although she explains that men may fulfill the role of Mother in this metaphorical unit. 17 Indeed, as I noted above 18 (and as the book’s title highlights), Fineman is quite critical of feminists who have deleted gender from the role of mother. 19 Fineman’s thesis might suggest instead the unifying theme of valuing mothers’ work in the home. Fineman argues compellingly that women have shouldered the inevitable costs of dependency and should be compensated for it. 39 Her focus on the mother/child dyad appears to be different from some feminists’ focus on the workplace. [Johanna Brenner], for example, argues that [i]n a period where the vast majority of women with young children work for wages, a welfare policy that pays women to stay home is anachronistic. 40 Brenner contends that it is women’s increasing access to paid work that has freed women from depending on men for economic support, thereby enabling the feminist challenge to traditional gender ideology. 41 She therefore advocates a strategy centered on providing working mothers with support rather than demanding payments for women to stay home with their children. 42 In using motherhood’s power for political ends, feminists will have to explore further the value of mothers’ work in the home and its relationship to women’s wage labor.